Cybersecurity for Sustainable Internet of Things Implementation in Healthcare - Teodora Bakardjieva; Antonina Ivanova; Yanko Yankov; Zhivko Zhekov (International Journal Bioautomation)
The current systematic review aims to summarise and discuss the impact and implications of the Internet of Things (IoT) in the healthcare sector. An electronic search for articles using Google Scholar, PubMed, and Scopus was conducted from January 1, 2019, up to July 1, 2024, under Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review presents cybersecurity threats in IoT-based healthcare infrastructure and applications that enable smart healthcare services to operate. When collecting and storing medical data from IoT sensors, there is an opportunity to analyse this data, which can improve the identification of risk factors, diagnosis of diseases, treatment, and remote monitoring, which creates prerequisites for reliable self-monitoring by patients. Advantages and risks have been evaluated, and recommendations for further research have been suggested. IoT provides an opportunity to improve the quality and efficiency of the entire service delivery ecosystem, including hospital management, medical asset management, staff workflow monitoring, and optimisation of medical resources based on patient flow.